2019
DOI: 10.1016/j.dhjo.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Is there a standard procedure for assessing and providing assistive devices for people with neuro-disabling conditions in United Kingdom? A nation-wide survey

Abstract: Standardized operating procedures for assistive device provision are not being carried out within the UK. Variable access to assistive devices supplied by the state indicates inequity across regions. Future research should explore potential benefits of developing standardized assessment procedures for the provision of assistive devices and devise methods to reduce current variability in service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
5
0
2
Order By: Relevance
“…To this end, a considerable time and effort is needed by an interdisciplinary team that includes many trials with different variables of SIT setup. On the contrary, assistive technology professionals require a benchmark application [9], which is compatible with most SITs, to make a better comparison and evaluation automatically with standardized tests under the same conditions. Considering the increasing number of SIT users, any tool that allows a more accurate and quicker SIT evaluation process becomes an important requirement day by day.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a considerable time and effort is needed by an interdisciplinary team that includes many trials with different variables of SIT setup. On the contrary, assistive technology professionals require a benchmark application [9], which is compatible with most SITs, to make a better comparison and evaluation automatically with standardized tests under the same conditions. Considering the increasing number of SIT users, any tool that allows a more accurate and quicker SIT evaluation process becomes an important requirement day by day.…”
Section: Introductionmentioning
confidence: 99%
“…Acerca de questionamentos ainda presentes na literatura sobre atributos de adaptadores para o lápis que influenciam na percepção de satisfação com o dispositivo e com o desempenho na escrita, o presente estudo oferece indicativos para TO e educadores que favorecem a escolha de adaptadores para escolares que deles necessitem, incluindo o escolar na escolha do produto. Além disso, o acompanhamento do recurso de TA é fundamental para garantir que a intervenção seja adequada e não ocorra abandono (TRICCAS et al, 2019).…”
Section: Discussionunclassified
“…The second element to which the reviews point is that a structured and systematic process conducted by professionals with experience in AT seems to be an important factor in an effective AT service delivery and in having satisfied users (Brandt et al, 2014(Brandt et al, , 2015(Brandt et al, , 2020Larsson Ranada and Lidström, 2019;Socialstyrelsen, 2015). Some studies have suggested that, if service delivery is to be evidence-based, it should rely on systematic and structured procedures that should be based on guidelines, instruments, or models (Bernd et al, 2009;Triccas et al, 2019). Within this field, models are understood as symbolic representations of concepts that support and guide the AT service delivery (Bernd et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%